PEMANTAUAN DAN EVALUASI TEKNOLOGI INFORMASI DI PEMERINTAH KABUPATEN GRESIK BERDASARKAN PERATURAN MENTERI PAN-RB NOMOR 59 TAHUN 2020 - Dewi, Renny Sari; Astiarasanti, Amelia Hayyu; Fahmi, Fiqih Zulfikar (Journal of Digital Business and Innovation Management, 2022)
Abstract Central government agencies until the current local government have started to implement an electronic-based governance system (SPBE). SPBE is a government organization that utilizes information and communication technology to provide services to SPBE Users. The government has established SPBE guidelines stipulated in Presidential Regulation No. 95 of 2018 on SPBE and to ensure the implementation of SPBE can run to achieve its objectives to realize an integrated and comprehensive government set forth The Ministerial Regulation of PAN-RB No. 5 of 2018 concerning SPBE Evaluation Guidelines. In 2019, the Ministry of PAN-RB conducted SPBE evaluation activities through the SPBE self-assessment method and obtained SPBE index results worth 3.14 on a scale of 0-5 and entered into the GOOD predicate. From these results, the Gresik district government needs to improve the quality of SPBE. In September 2020 the Government again established The Ministerial Regulation of PAN-RB No. 59 of 2020 concerning the monitoring and evaluation of SPBE. The regulation has been listed 4 Domains, 8 Aspects, and 47 indicators to assess the maturity level of SPBE. The result of the evaluation maturity level of SPBE evaluation of Gresik district government based on Regulation of the Minister of PAN-RB Number 59 of 2020 is 2.54. Interpretation of the value of maturity level is included in the Predicate Enough is the level of maturity of the process capability occupied level 2 (managed) and the level of service capability occupied level 2 (Interaction). Keywords: SPBE; Monitoring and Evaluation; IT Audit; Ministerial Regulation of PAN-RB Number 59 of 2020